Perfil de infecções bacterianas do trato urinário e resistência aos antibióticos - Lima, Andréa Danielle Parreiras (2017)
Urinary tract infection (UTI) is the invasion, multiplication and colonization by bacteria from part of the urinary system. Uroculture is considered the gold standard for laboratory diagnosis of UTI, through which it is possible to identify the formation of bacterial colonies and the causative agent of infection. After the uroculture, it is indicated the accomplishment of the antibiogram, which allows to know the sensitivity or resistance of the bacterium to the main antibiotics used. The treatment of UTI most often is empirical, which contributes to the development of resistance of major causative bacteria to frequently used antibiotics. Knowledge of the prevalence and frequency of infectious agents facilitates the optimization of treatment, thus reducing the appearance of new bacterial resistance. To this end, epidemiological studies must be carried out periodically, since data on the development of antibiotic resistance vary widely between regions and over time. The objective of this study was to trace the profile of patients most affected by urinary tract infections, to identify the main causative agents and to evaluate the antibiotic resistance profile of bacteria isolated from urocultures. A retrospective epidemiological study was carried out by analyzing the results of urocultures and their respective antibiograms, contained in the database of a private clinical analysis laboratory, located in the city of Uberlândia-MG, from 2012 to 2016. The information collected for analysis was sex, age, date and results of the examinations of patients of community origin. Of the positive results, the majority belonged to female patients and the most frequent bacterium was Escherichia coli. The most affected age group was over 60 years, with 48.5% of the total. Antibiotics that showed within the indicated resistance limit for the treatment of urinary tract infection caused by E. coli were the fluoroquinolones (ciprofloxacin, levofloxacin and norfloxacin), amoxicillin/clavulanic acid and imipenem. Sulfamethoxazole-trimethoprim presented resistance of approximately 50% for all bacteria analyzed, and ampicillin was one of the most resistant antibiotics.